The Gambia : An Assessment of the Investment Climate - World Bank (Washington, DC, 2013)
The situation in The Gambia is a good example of the many challenges small states have to deal with. The country is faced with institutional capacity constraints and due to a narrow resource base and a small domestic market, its production base and exports show little diversification. Like other small states, the country tends to rely heavily on external trade and foreign investment to overcome its scale and resource limitation, increasing its vulnerability to external shocks. The objective of this report is to analyze the investment climate of The Gambia in its every dimension. It is the first time such a comprehensive report is prepared by the World Bank about the investment climate in The Gambia. Recent World Bank reports only look at specific areas of the investment climate and do not provide a global assessment of investment climate issues based on firm level data as does this report. A final and brief chapter provides a synthesis of the report and some strategic directions aimed at improving the business environment in the country.